Thermodynamic Hadron-Quark Phase Transition of Chiral Nuclear Matter to Quark-Gluon Plasma - Tuan Anh, Nguyen (Communications in Physics, 2017)
After receiving very interesting results from investigations of chiral nuclear matter based on the extended Nambu-Jona--Lasinio model (ENJL) included the scalar-vector eight-point interaction, a fundamental question of nuclear physics is what happens to chiral nuclear matter as it is compressed or heated. At very high density and temperature, quarks and gluons come into play and a transition is expected to happen from a phase of nuclear matter consisting of confined hadrons and mesons to a state of `liberated' quarks and gluons. In this paper, we investigate the hadron-quark (HQ) phase transition occurs beyond the chiral phase transition in the nuclear matter. The results show that there exits a quarkyonic-like phase, appeared just before deconfinement, when the chiral symmetry is restored but the elementary excitation modes are still nucleonic